Pengaruh Kinerja Keuangan, Ukuran Perusahaan, dan Pandemi Covid-19 Terhadap Return Saham - Aini, Sania Qurrotu; Triyono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this study is to determine how finansial performance, company size, and the COVID-19 pandemic affect stock returns on the LQ 45 IDX for the period 2019 to 2021. Information on the company’s annual report can be found at www.idx.co.id, http://finance.yahoo.com, and the company’s official website. Collected 69 data using purposive sampling method. Multiple linear regression, R-square, and t-statistic test were the data analysis processed using SPSS 25. It was gathered that current ratio, debt to equity ratio, firm size, and COVID-19 pandemic all had an impact on stock returns. On the other hand, return on equity and total aset turnover have no affect on stock return.